Design de superfície: estampas para decoração - Souza, Florency Kamimura (2013)
The work explores aspects of surface design related to textile printing that is of influence to the work of graphic artists who wants to develop a project in this area that is still not widely known. For this, research is presented on the history of textile printing, color harmonies, trends, printing processes and how a rapport works. The result of the theoretical work can be seen in the development of a mini-collection of prints for interior decoration.